Ethyl methane sulfonate induced mutations in M2 generation and physiological variations in M1 generation of peppers (Capsicum annuum L.) - Arisha, Mohamed H.; Shah, Syed N. M.; Gong, Zhen-Hui; Jing, Hua; Li, Chao; Zhang, Huai-Xia (Frontiers in Plant Science, 2015)
This study was conducted to enhance genetic variability in peppers (Capsicum annuum, cv B12) using ethyl methansulphonate (EMS). Exposure to an EMS concentration of 0.6%, v/v for 12 hours was used to mutagenize 2000 seeds for the first generation (M1). It was observed that the growth behaviors including plant height, flowering date and number of seeds per first fruit were different in the M1 generation than in wild type plants. In addition one phenotypic mutation (leaf shape and plant architecture) was observed during the M1 generation. During the seedling stage in the M2 generation, the observed changes were in the form of slow growth or chlorophyll defect (e.g., albino, pale green and yellow seedlings). At maturity, there were three kinds of phenotypic mutations observed in three different families of the mutant population. The first observed change was a plant with yellow leaf color, and the leaves of this mutant plant contained 62.19% less chlorophyll a and 64.06% less chlorophyll b as compared to the wild-type. The second mutation resulted in one dwarf plant with a very short stature (6 cm), compact internodes and the leaves and stem were rough and thick. The third type of mutation occurred in four plants and resulted in the leaves of these plants being very thick and longer than those of wild type plants. Furthermore, anatomical observations of the leaf blade section of this mutant plant type contained more xylem and collenchyma tissue in the leaf midrib of the mutant plant than wild type. In addition, its leaf blade contained thicker palisade and spongy tissue than the wild type.